“Producción de humus de lombriz mediante el aprovechamiento del raquis del orito (Musa acuminata) en el cantón La Maná recinto San José del Estero”. - Chugchilan Baraja, Genaro Orlando (2021)
The production of humus through the Californian red worm is a biotechnology that uses this domesticated species as a work tool to recycle all types of organic matter, in this way it is intended to evaluate the production of earthworm humus by taking advantage of the rachis of the orito (Musa acuminata) in La Maná canton, San José del Estero area, for this, four treatments were used based on garden soil, rachis of banana orito, bovine manure and litter, each treatment had five repetitions, a completely random design was used. (DCA) and Duncan multiple range test was applied at 5% probability, the variables were evaluated during 18 weeks and were: temperature, humidity, p H, composting performance and nutritional quality of the compost and the components. The highest temperature, p H and weight of humus was recorded in the treatment Soil from orchard 6.81 kg + Orito rachis 11.36 kg + Bovine manure 25.00 kg + litter 4.54 kg at 23.44 ° C; 8.08 and 37.50 kg respectively. The highest concentration of nitrogen and phosphorus was recorded in the Soil from orchard treatment 6.81 + Orito raquis 25.00 kg + bovine manure 11.36 kg + litter 4.54 kg with 0.90 and 0.20%, in the case of potassium was registered with the Soil from orchard treatment 6.81 + Orito rachis 20.45 kg + bovine manure 15.90 kg + 4.54 kg litter with 0.76%. The highest income and benefit / cost ratio were registered in the Soil from orchard treatment 6.81 + Orito raquis 11.36 kg + bovine manure 25.00 kg + litter 4.54 kg with 56.25 USD and 0.12. This technology allows the recycling of nutrients to the soil and helps the development and growth of vegetables.